SOX2-mediated upregulation of CD24 promotes adaptive resistance toward targeted therapy in melanoma - Hüser, Laura; Sachindra, Sachindra; Granados, Karol; Federico, Aniello; Larribere, Lionel; Novak, Daniel; Umansky, Viktor; Altevogt, Peter; Utikal, Jochen (International journal of cancer, 2018)
Melanoma is often characterized by a constitutively active RAS-RAF-MEK-ERK pathway. For targeted therapy, BRAF inhibitors are available that are powerful in the beginning but resistance occurs rather fast. A better understanding of the mechanisms of resistance is urgently needed to increase the success of the treatment. Here, we observed that SOX2 and CD24 are upregulated upon BRAF inhibitor treatment. A similar upregulation was seen in targeted therapy-resistant, melanoma-derived induced pluripotent cancer cells (iPCCs). SOX2 and CD24 are known to promote an undifferentiated and cancer stem cell-like phenotype associated with resistance. We, therefore, elucidated the role of SOX2 and CD24 in targeted therapy resistance in more detail. We found that the upregulation of SOX2 and CD24 required activation of STAT3 and that SOX2 induced the expression of CD24 by binding to its promoter. We find that the overexpression of SOX2 or CD24 significantly increases the resistance toward BRAF inhibitors, while SOX2 knock-down rendered cells more sensitivity toward treatment. The overexpression of CD24 or SOX2 induced Src and STAT3 activity. Importantly, by either CD24 knock-down or Src/STAT3 inhibition in resistant SOX2-overexpressing cells, the sensitivity toward BRAF inhibitors was re-established. Hence, we suggest a novel mechanism of adaptive resistance whereby BRAF inhibition is circumvented via the activation of STAT3, SOX2 and CD24. Thus, to prevent adaptive resistance, it might be beneficial to combine Src/STAT3 inhibitors together with MAPK pathway inhibitors.